2003
DOI: 10.1002/ajmg.a.20596
|View full text |Cite
|
Sign up to set email alerts
|

Cloacal exstrophy in an infant with 9q34.1‐qter deletion resulting from a de novo unbalanced translocation between chromosome 9q and Yq

Abstract: Cloacal exstrophy is a rare malformation, belonging to a spectrum of birth defects, which, in order of severity, includes phallic separation with epispadias, pubic diastasis, bladder exstrophy, and cloacal exstrophy. This malformation overlaps the OEIS complex (O = omphalocele, E = bladder exstrophy, I = imperforate anus, S = spinal defects). The etiology of cloacal exstrophy is unknown to date. It may result from either a single defect of early blastogenesis or a defect of mesodermal migration during the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
35
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 25 publications
2
35
0
1
Order By: Relevance
“…In conclusion, the present description of a 3q interstitial deletion and the report by Thauvin-Robinet et al [2004] describing a 9q terminal deletion give further credence to the concept that genetic defects may be responsible for the pathogenesis of cloacal exstrophy/OEIS complex and indicate potential loci for the putative genes. …”
supporting
confidence: 65%
See 1 more Smart Citation
“…In conclusion, the present description of a 3q interstitial deletion and the report by Thauvin-Robinet et al [2004] describing a 9q terminal deletion give further credence to the concept that genetic defects may be responsible for the pathogenesis of cloacal exstrophy/OEIS complex and indicate potential loci for the putative genes. …”
supporting
confidence: 65%
“…In your journal, Thauvin-Robinet et al [2004] recently reported a case of cloacal exstrophy with a de novo unbalanced translocation between the long arm of chromosome 9 and the long arm of chromosome Y, resulting in a 9q34.1-qter deletion [Thauvin-Robinet et al, 2004]. They argued that their case represented the first report of cloacal exstrophy accompanied by an unbalanced chromosomal defect and that their observation supported the notion that genetic defect(s) may be responsible for the pathogenesis of cloacal exstrophy.…”
mentioning
confidence: 97%
“…3 OEIS complex has been shown to be associated with Opitz/BBB syndrome, Goltz syndrome, trisomy 18, oculo-auriculo-vertebral syndrome, frontonasal dysplasia, 4 mutations in mitochondrial 12S rRNA, 5 and mutations in homeobox genes such as HLXB9. 6,7 Recently, Thauvin-Robinet et al 8 reported an infant with cloacal exstrophy and a 9q34.1-qter deletion, and Kosaki et al 9 reported a term baby with OEIS complex and a 3q12.2-q13.2 deletion.…”
Section: Discussionmentioning
confidence: 97%
“…Analyses of genes suggested as candidates by rare chromosomal aberrations, co-occurring syndromes or syndromes with phenotypic overlap, seem rational, but yet have failed to identify causative mutations (5,(28)(29)(30)(31)(32)(33). Comparative genomic hybridization in a CBE family has only identified a known copy-number variant, most likely unrelated to the phenotype (34) and linkage studies have not identified strong candidate loci (26,27).…”
Section: Discussionmentioning
confidence: 99%